Institutional fit and river basin governance: A new approach using multiple composite measures - Louis Lebel (2018)
The notion that effective environmental governance depends in part on achieving a reasonable fit between institutional arrangements and the features of ecosystems and their interconnections with users has been central to much thinking about social-ecological systems for more than a decade. Based on expert consultations this study proposes a set of six dimensions of fit for water governance regimes and then empirically explores variation in measures of these in 28 case studies of national parts of river basins in Europe, Asia, Latin America, and Africa drawing on a database compiled by the Twin2Go project. The six measures capture different but potentially important dimensions of fit: allocation, integration, conservation, basinization, participation, and adaptation. Based on combinations of responses to a standard questionnaire filled in by groups of experts in each basin we derived quantitative measures for each indicator. Substantial variation in these measures of fit was apparent among basins in developing and developed countries. Geographical location is not a barrier to high institutional fit; but within basins different measures of fit often diverge. This suggests it is difficult, but not impossible, to simultaneously achieve a high fit against multiple challenging conditions. Comparing multidimensional fit profiles give a sense of how well water governance regimes are equipped for dealing with a range of natural resource and use-related conditions and suggests areas for priority intervention. The findings of this study thus confirm and help explain previous work that has concluded that context is important for understanding the variable consequences of institutional reform on water governance practices as well as on social and environmental outcomes. © 2013 by the author(s).